Temporary streams in temperate zones: recognizing, monitoring and restoring transitional aquatic‐terrestrial ecosystems - Stubbington, Rachel; England, Judy; Wood, Paul J.; Sefton, Catherine E.M. (Wiley interdisciplinary reviews. Water, 2017)
Temporary streams are defined by periodic flow cessation, and may experience partial or complete loss of surface water. The ecology and hydrology of these transitional aquatic‐terrestrial ecosystems have received unprecedented attention in recent years. Research has focussed on the arid, semi‐arid, and Mediterranean regions in which temporary systems are the dominant stream type, and those in cooler, wetter temperate regions with an oceanic climate influence are also receiving increasing attention. These oceanic systems take diverse forms, including meandering alluvial plain rivers, ‘winterbourne’ chalk streams, and peatland gullies. Temporary streams provide ecosystem services and support a diverse biota that includes rare and endemic specialists. We examine this biota and illustrate that temporary stream diversity can be higher than in comparable perennial systems, in particular when differences among sites and times are considered; these diversity patterns can be related to transitions between lotic, lentic, and terrestrial instream conditions. Human impacts on temperate‐zone temporary streams are ubiquitous, and result from water‐resource and land‐use‐related stressors, which interact in a changing climate to alter natural flow regimes. These impacts may remain uncharacterized due to inadequate protection of small temporary streams by current legislation, and hydrological and biological monitoring programs therefore require expansion to better represent temporary systems. Novel, temporary‐stream‐specific biomonitors and multi‐metric indices require development, to integrate characterization of ecological quality during lotic, lentic, and terrestrial phases. In addition, projects to restore flow regimes, habitats, and communities may be required to improve the ecological quality of temporary streams. WIREs Water 2017, 4:e1223. doi: 10.1002/wat2.1223 This article is categorized under: Water and Life > Conservation, Management, and Awareness Water and Life > Nature of Freshwater Ecosystems Water and Life > Stresses and Pressures on Ecosystems Science of Water > Water Extremes Temporary streams transition between flowing, pool, and dry phases, and this environmental variability supports high biodiversity. However, human activities have altered flow intermittence regimes and reduced temporary stream health. Novel biomonitoring approaches combining assessment of flowing, pool, and dry phases are needed to characterize ecosystem health and identify restoration priorities.